2021
DOI: 10.3389/fmats.2021.792299
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic–Complementary Use of Industrial Solid Wastes to Prepare High-Performance Rapid Repair Mortar

Abstract: With the vigorous development of infrastructure engineering, there are growing demands for high-performance rapid repair mortar, especially those using environmental-friendly and low-carbon cementitious materials. Hereupon, this work explored an innovative approach for rapid repair mortar preparation using solid waste-based calcium sulfoaluminate cement. The calcium sulfoaluminate cement was first prepared via synergetic–complementary use of industrial solid wastes and then adopted to prepare rapid repair mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Dong et al [24], Liu et al [25] found that alkali exciters could effectively promote the dissolution and hydration reactions of silicates and aluminates in lithium slag, which in turn improved the volcanic ash activity of lithium slag and help to improve the compressive strength of lithium-slag-cement-based cementitious materials and their durability performance. In addition, Shen et al [26] found that alkaline exciter dosing significantly affected the lithium slag activity. Wu [18] and Wang et al [27] found that high-temperature complex alkali excitation was more effective in improving the activity of lithium slag.…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al [24], Liu et al [25] found that alkali exciters could effectively promote the dissolution and hydration reactions of silicates and aluminates in lithium slag, which in turn improved the volcanic ash activity of lithium slag and help to improve the compressive strength of lithium-slag-cement-based cementitious materials and their durability performance. In addition, Shen et al [26] found that alkaline exciter dosing significantly affected the lithium slag activity. Wu [18] and Wang et al [27] found that high-temperature complex alkali excitation was more effective in improving the activity of lithium slag.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the life-cycle assessment results indicated that this approach was environmentally friendly, cost-effective, and resource-efficient. 18 Our previous work comprehensively studied the influence of different additives on the performance of RRM and an obtained optimized preparation method. 19 These studies showed that an SAC-based RRM can achieve excellent mechanical strengths and good workability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Li et al successfully prepared RRM with high mechanical strengths using solid WSAC, and the 2 h compressive and flexural strengths and 1-day bonding strength of the prepared RRM reached 32.5, 9.2, and 2.01 MPa, respectively. Meanwhile, the life-cycle assessment results indicated that this approach was environmentally friendly, cost-effective, and resource-efficient . Our previous work comprehensively studied the influence of different additives on the performance of RRM and an obtained optimized preparation method .…”
Section: Introductionmentioning
confidence: 99%